Paging and Location Management in IEEE 802.16j Multihop Relay Network. (9th February 2010) - Lin, Kuan-Po; Wei, Hung-Yu
Abstract : IEEE 802.16j is an emerging wireless broadband networking standard that integrates infrastructure base stations with multihop relay technology. Based on the idle mode operation in IEEE 802.16j, we propose a novel location management and paging scheme. It integrates the paging area-based and the timer-based location update mechanism. In paging area-based scheme, an idle mode mobile station updates when it moves to a new paging area. In timer-based scheme, an idle mode MS updates when the location update timer expires. In this work, we formulate the mathematical model to evaluate the performance of the proposed paging scheme. A new random walk mobility model that is suitable for modeling in multihop relay network is created. Optimization of location update timer is also investigated.